Multiple strategies association revealed functional candidate FASN gene for fatty acid composition in cattle - Bo Zhu; Tianzhen Wang; Qunhao Niu; Zezhao Wang; El Hamidi Hay; Lei Xu; Yan Chen; Lupei Zhang; Xue Gao; Huijiang Gao; Yang Cao; Yumin Zhao; et al. (Communications Biology)
Abstract Fatty acid composition (FA) is an important indicator of meat quality in beef cattle. We investigated potential functional candidate genes for FA in beef cattle by integrating genomic and transcriptomic dataset through multiple strategies. In this study, we observed 65 SNPs overlapping with five candidate genes (CCDC57, FASN, HDAC11, ALG14, and ZMAT4) using two steps association based on the imputed sequencing variants. Using multiple traits GWAS, we further identified three significant SNPs located in the upstream of FASN and one SNP (chr19:50779529) was embedded in FASN. Of those, two SNPs were further identified as the cis-eQTL based on transcriptomic analysis of muscle tissues. Moreover, the knockdown of FASN yielded a significant reduction in intracellular triglyceride content in preadipocytes and impeded lipid droplet accumulation in adipocytes. RNA-seq analysis of preadipocytes with FASN interference revealed that the differentially expressed genes were enriched in cell differentiation and lipid metabolic pathway. Our study underscored the indispensable role of FASN in orchestrating adipocyte differentiation, and fatty acid metabolism. The integrative analysis with multiple strategies may contribute to the understanding of the genetic architecture of FA in farm animals.